Pharmacokinetics of L-theanine and the effect on amino acid composition in mice administered with L-theanine - Shinnosuke Yamaura; Koki Sadamori; Reiko Konishi; Takashi Majima; Akira Mukai; Kyosuke Uno; Toshihiko Kinjo; Koji Komori; Nobuyuki Kuramoto; Kou Kawada (Amino Acids)
Abstract L-theanine, an amino acid component of the tea leaves of Camellia sinensis, is sold in Japan as a supplement for good sleep. Although several studies in humans and mice have reported the effects of L-theanine on brain function, only a few reports have comprehensively clarified the disposition of theanine administered to mice and its effects on concentrations of other blood amino acids. In this study, we aimed to determine the changes in the blood levels of L-theanine administered to mice and amino acid composition of the serum. L-theanine were administered to four-week-old Std-ddY male mice orally or via tail vein injection. L-theanine and other amino acids in serum prepared from blood collected at different time points post-dose were labeled with phenylisothiocyanate and quantified. The serum concentration of orally administered L-theanine peaked 15 min after administration. The area under the curve for tail vein injection revealed the bioavailability of L- theanine to be approximately 70%. L-theanine administration did not affect any amino acid levels in the serum, but a significant increase in the peak area overlapping the Glycine (Gly) peak was observed 30 min after administration. L-theanine administered to mice was rapidly absorbed and eliminated, suggesting that taking L-theanine as a supplement is safe without affecting its own levels or serum levels of other amino acids. However, considering that Gly, similar to L-theanine, is used as a dietary supplement for its anxiolytic effects and to improve sleep, determining the effects of L-theanine administration on Gly is important and needs further research.